Pemanfaatan Gamelan Digital sebagai Upaya Peningkatkan Kreativitas Mahasiswa PGMI - Alfian Eko Widodo Adi Prasetyo; Rakanita Dyah Ayu Kinesti; Fajry Sub'haan Syah Sinaga (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2023)
Purpose: This study aims to see the increase in student creativity in SBDP courses on music art material. Involving 45 PGMI FITK UIN Sunan Kalijaga students consisting of 2 rombel, and grouped in 1 experimental class and 1 control class. Method: The method used is quantitative discretive t test to see the comparison of experimental and control classes. Result and Discussion: Based on the results of the analysis and research hypothesis, it shows that learning SBDP digital music material has been proven to increase student creativity. Observation data obtained that before the action was taken there were 45% of students who had not increased their creativity and there were 55% of children who began to develop their creativity abilities. After taking action in cycles I, II and III, it was obtained that the increase in creativity ability in the experimental class was 67.45% and 22.12% in the control class. The results of this study can see the differences and creativity abilities of students in using smartphone technology in SBDP courses on the theme of digital gamelan music.